Effect of subacute administration of orange juice (Citrus sinensis) on duodenal structure in paediatric Sprague-Dawley rats (Rattus novergicus) - Yan, Teo Qin; Hendry, Altaff; Andre, Daniel Latief; Rahman, Muhammad Luthfi; Rudramurti, Win Satya; Permana, Nadine Hanifa; Utami, Dian Maulia; Setiyono, Agus; Pristihadi, Diah Nugrahani (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2024)
This research investigates the impact of orange juice consumption on the histological structure of the duodenum, a critical site for nutrient absorption and digestion. Focusing on pediatric animals, orange juice (with a pH of 3) was administered to post-weaning rats aged 4 weeks to 6 weeks at dosages ranging from 0g/kg BW to 20g/kg BW over two weeks. Duodenal histopathology was assessed, focusing on parameters such as the quantity of crypts of Lieberkuhn, as well as the length, height, width, and depth of villi (measured in μm). Anatomical pathology examination included measurements of the length and width of the duodenum (also in μm), as well as the color mean (OD). The research findings indicate no significant changes in histo-pathology or anatomy pathology of the duodenum. This suggests that young individuals can adapt to acidic challenges without compromising gastrointestinal health. These findings offer reassurance regarding the short-term consumption of acidic orange juice (with a pH of 3) with minimal risks to intestinal integrity, both during growth and development.